Sweet pepper production under greenhouse conditions: correlation among plant density and yield variables - Monge Pérez, José Eladio (2021)
For sweet pepper (Capsicum annuum) cv. FBM-9 grown under greenhouse conditions and using two pruning systems (Spanish and Dutch), the researchers estimated Pearson correlations among plant density and the following variables:  number of fruits per plant and per square meter, fruit weight (g), and total and commercial yield (ton/ha). The crop was planted on coconut fiber as substrate, and managed with fertigation.  There were 10 statistically significant Pearson correlations (p≤0,05).  In those cases the linear regression statistics were calculated.  Independently of pruning system, there was significant correlation between plant density and:  number of noncommercial fruits per plant (r = -0,55**); number of first quality fruits per square meter (r = 0,58**); total yield (r = 0,42*); first quality yield (r = 0,65**); and commercial yield (r = 0,43*).  Furthermore, only for Spanish pruning treatments there was significant correlation between plant density and:  number of second quality fruits per plant (r = -0,59*); fruit weight (r = 0,76**); and first quality fruit weight (r = 0,62*).  It is concluded that the use of a higher plant density is the best option for growers, from an economical point of view.  It is recommended to evaluate higher plant densities than those used in this trial (2,60-3,90 plants/m2), to determine the optimum plant density.